MIFOPOETICAL CHRONOTOPE AS A SEMANTIC CATEGORYWORKS ON THE HISTORY OF THE GENUS - Tkachyk, N. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article investigates the theoretical aspects of time-space in mythopoetic novels, where is the story of the genus: defines the key spatial dominant; disclosed specifics of artistic time; outlines mechanisms influence individual mifopoetical motive on specific time-space.